1974
DOI: 10.1084/jem.140.3.837
|View full text |Cite
|
Sign up to set email alerts
|

On the Relation of Products of Activated Lymphocytes to Cell-Mediated Cytolysis

Abstract: Experiments have been designed to test the hypothesis that soluble mediator production and T-cell-mediated cytotoxicity are necessarily related phenomena, and that soluble mediators may be involved in the mechanism of cytolysis. To this end, agents known to inhibit T-cell-mediated lysis in vitro have been studied for their effects on the production of two lymphocyte-derived mediators, lymphotoxin (LT) and migration inhibitory factor (MIF). A clear dissociation between mediator production and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1975
1975
2003
2003

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Since protein synthesis is known to be necessarj' for the function of cytotoxic T cells (9), it was necessar)-to use an inhibitor of protein synthesis that was irreversible in its action, so that excess inhibitor could be washed out of the system before immune spleen cells were added-Pactamycin inhibits the process of initiation of protein synthesis (10) and at high concentrations prevents the translocation event (23). It has also been reported (18) to be largely irreversible in its action. This was confirmed as follows.…”
Section: Effect Of Inhibition Of Early Protein Synthesis In Target Cellsmentioning
confidence: 95%
“…Since protein synthesis is known to be necessarj' for the function of cytotoxic T cells (9), it was necessar)-to use an inhibitor of protein synthesis that was irreversible in its action, so that excess inhibitor could be washed out of the system before immune spleen cells were added-Pactamycin inhibits the process of initiation of protein synthesis (10) and at high concentrations prevents the translocation event (23). It has also been reported (18) to be largely irreversible in its action. This was confirmed as follows.…”
Section: Effect Of Inhibition Of Early Protein Synthesis In Target Cellsmentioning
confidence: 95%
“…This may be due to a dissociated development of delayed hypersensitivity against cellular antigens, accompanied by competitive suppression of cytotoxicity against the same antigens. This explanation seems plausible since Tigelaar and Gorczynski [22] have reported that delayed hypersensitivity and cytotoxicity are mediated by distinct subpopulations of T cells and Henney et al [8] have reported that T cell-mediated cytolysis and production of chemical mediators can be dissociated by the use of inhibitors of protein synthesis.…”
Section: Discussionmentioning
confidence: 98%
“…This may be due to a dissociated development of delayed hypersensitivity against cellular antigens, accompanied by competitive sup-pression of cytotoxicity against the same antigens. This explanation seems plausible since Tigelaar and Gorczynski [22] have reported that delayed hypersensitivity and cytotoxicity are mediated by distinct subpopulations of T cells and Henney et al [8] have reported that T cell-mediated cytolysis and production of chemical mediators can be dissociated by the use of inhibitors of protein synthesis.…”
Section: Discussionmentioning
confidence: 99%